Clinical and anatomopathological alterations found in a dog positive for Canine Visceral Leishmaniasis in the Municipality of Varginha, Minas Gerais - Guedes, Elizangela; Carioca de Souza, Bruna; Ribeiro Pedrosa, Gabriela; Santana Gonçalves, Elaine; Lourenço Batista, Raphaela Aparecida; Pereira Lopes, Lara; Fortunato de Lima, Scarlet; Mambeli Balieiro, José Eduardo (Spei Domus, 2021)
Canine Visceral Leishmaniasis is a severe disease with a worldwide distribution and high morbidity and mor-tality. In addition to its zoonotic character, the clinical symptomatology is variable and even non-existent, re-quiring the Veterinarian to carefully interpret the physical and anatomopathological changes. In this sense, the study aimed to describe the physical examination and necropsy findings in a six-year-old mongrel bitch, from the shelter of the Zoonosis Control Center in the city of Varginha/MG, seropositive for Visceral Leishmaniasis. The results revealed physical and necropsy findings consistent with a positive serological diagnosis for Canine Visceral Leishmaniasis. In this way, control and prevention measures aimed at stray animals and residents in animal shelters become important, since dogs are important in the epidemiology of Human Leishmaniasis. It is up to the veterinarian to identify positive animals and implement the concept of one health